Implementation of Financial Risk Management in Improving the Company's Financial Stability - Shalihah, Mar'atun; Situmorang, Tumpal P.; Yusnita, Yusnita; Ridwan; Kalsum, Ummy; Wahyudiyono, Wahyudiyono (Maneggio, 2024)
This research examines the implementation of financial risk management and its impact on improving the financial stability of companies. Financial risk management is a critical process for identifying, assessing, and mitigating risks that may affect a company's financial health. In today’s dynamic and often uncertain market environment, effective risk management is essential for ensuring the long-term survival and profitability of businesses. This study focuses on various risk management strategies employed by companies, such as risk identification, analysis, mitigation, and monitoring, and explores how these strategies contribute to maintaining financial stability. Using a combination of quantitative methods, data was collected through surveys and analyzed using regression analysis to determine the relationship between risk management practices and financial stability. The findings reveal that companies with structured and proactive financial risk management systems exhibit higher levels of financial stability. This research provides valuable insights for business leaders seeking to improve their financial risk management practices and enhance their company's financial resilience.